Establishing the reference value for tibial tubercle-trochlear groove distance on MRI in Southern Chinese population and its correlation with age, sex, height, weight and size: A multi-centre study - Kwun Man Cyrus Mo; Kwan Yin Francis Cho; Ka Yan Alice Au; Ka Yin Gregory Lee; Hei Man Joyce Cheng (Journal of Orthopaedics, Trauma and Rehabilitation)
Objective: The first objective of this study is to determine the reference Tibial Tubercle-Trochlear Groove (TT-TG) distance on MRI in Southern Chinese population. The second objective is to investigate the correlation between TT-TG distance and (i) age, (ii) sex, (iii) height, (iv) weight and (v) Body Mass Index (BMI) respectively. Method: Three hundred MRI knees performed in two different centres between August 2017 and October 2018 were included. All patients were prospectively recruited after MRI referral from Orthopaedics department. The TT-TG distances were measured by two radiologists independently. Measurement reliability was assessed using intraclass correlation coefficient (ICC). One sample t -test was used to compare the results between this study and other published studies. Spearman’s rank correlation coefficient was used to determine correlations between the TT-TG distance and age, sex, height, weight and BMI respectively. Result: There was no statistical significance between the mean of TT-TG distances from the two radiologists ( P -value = 0.32). The measurement reliability was excellent (ICC = 0.922 ± 0.02). The mean of averaged TT-TG distance was 8.32 ± 0.33 mm (range 2.01 to 17.48 mm). There were no statistical significant differences in means of TT-TG distance between laterality and gender. There were statistically significant correlations between (i) TT-TG distance and age ( p -value = 0.009), and (ii) TT-TG distance and height ( p -value = 0.014). Conclusion: The reference TT-TG distance on MRI in Southern Chinese population was 8.32 ± 0.33 mm. Statistically significant correlations were established between (i) TT-TG distance and age; and (ii) TT-TG distance and height.